Prediction and Validation of a Druggable Site on Virulence Factor of Drug Resistant Burkholderia cenocepacia. Issue 40 (1st May 2021) - Lal, Kanhaya; Bermeo, Rafael; Cramer, Jonathan; Vasile, Francesca; Ernst, Beat; Imberty, Anne; Bernardi, Anna; Varrot, Annabelle; Belvisi, Laura
Abstract: Burkholderia cenocepacia is an opportunistic Gram‐negative bacterium that causes infections in patients suffering from chronic granulomatous diseases and cystic fibrosis. It displays significant morbidity and mortality due to extreme resistance to almost all clinically useful antibiotics. The bacterial lectin BC2L‐C expressed in B. cenocepacia is an interesting drug target involved in bacterial adhesion and subsequent deadly infection to the host. We solved the first high resolution crystal structure of the apo form of the lectin N‐terminal domain (BC2L‐C‐nt) and compared it with the ones complexed with carbohydrate ligands. Virtual screening of a small fragment library identified potential hits predicted to bind in the vicinity of the fucose binding site. A series of biophysical techniques and X‐ray crystallographic screening were employed to validate the interaction of the hits with the protein domain. The X‐ray structure of BC2L‐C‐nt complexed with one of the identified active fragments confirmed the ability of the site computationally identified to host drug‐like fragments. The fragment affinity could be determined by titration microcalorimetry. These structure‐based strategies further provide an opportunity to elaborate the fragments into high affinity anti‐adhesive glycomimetics, as therapeutic agents against B. cenocepacia . Abstract : A new druggable site for anti‐adhesive therapy . We used fragment‐based virtual screening to explore the druggability of a region in the vicinity of the fucose binding site in a lectin from an opportunistic and highly drug‐resistant pathogen. The crystal structure of the target protein complexed with the lead fragment validated the existence of a secondary binding site, paving the way for the design of potent ligands to be employed in anti‐adhesive therapy.